PREVALENCE OF APHIDOPHAGOUS HOVERFLIES (S YRPHIDAE: SYRPHINAE) I N RELATION TO THEIR PREY, GREEN APHIDS (MYZUS PERSICAE) O N BRASSICA (B RASSICA RAPA OLIEFERA) IN DADU - R. A. Jamali; N. Memom; M. A. Shah; K. Khan; A. Ansari (Journal of Animal and Plant Sciences, 2018)
During current investigation different fields of brassica crop present in district Dadu were explored systematically, from November 2016 to March 2017. The specimens were collected with the help of insect net, malaise trap and hand picking. Total 323 specimens of three species belonging to three different Genera of Aphidophagous Hoverflies were collected from green-peach aphid colonies (Myzus persicae) present on Brassica (brassica rapa oleifera) . 36.22 % of trapped hover flies were of Ischiodon scutellaris, 19.5% of Eupeodes luniger and 44.2 % of Episyrphus balteatus. In addition to this, 94 larvae of aphidophagous hover flies in the colonies of green peach aphid were also collected. In the current survey it was perceived that occurrence of these species varies from month to month due to significant effect of the ecological factors, with the average number being significantly increased as the temperature increased up to certain limits in winter, which shows positive correlation of hoverflies with temperature 0.444 % (P = 0.454) in winter. The number of syrphid flies was very low in November i.e. 7.4 % which gradually increased as the environment became favorable and the brassica became mature in the march i.e. 34.6 %. The population of syrphid flies was found to be significantly influenced by other ecological factors also. The Pearson correlation revealed strong negative correlation of aphidophagous hoverflies with humidity and wind speed 0.900 (P=0.038) and -0.835 (P = 0.078) respectively, while these hover flies had strong positive correlation with aphid colonies of Myzus persicae 0.975 (P =0.005). to oviposit near aphid colonies (Sadeghi and Gilbert,
Keywords: Correlation; Episyrphus balteatus; Prevalence; Myzus persicae; aphidophagous.